Comparative fragility methods for seismic assessment of masonry buildings located in Muccia (Italy). (September 2019) - Chieffo, Nicola; Clementi, Francesco; Formisano, Antonio; Lenci, Stefano
Abstract: The current paper focuses on a sector of the historic centre of Muccia, in the district of Macerata (Italy), affected by the seismic sequence that involved Central Italy in 2016. The main goal is comparison, in terms of fragility curves, among two vulnerability assessment methodologies (empirical and mechanical). The study area has been structurally and typologically identified according to the Building Typology Matrix (BTM). Physical vulnerability analysis of the urban-sector was performed through application of an index-based method, specifically for masonry building aggregates. An isolated masonry building, damaged after the seismic sequences, has been selected as a case study. For the assessed building, empirical fragility curves are presented according to Guagenti & Petrini's correlation law. Furthermore, a numerical model has been set up by using the macro-element approach, which has allowed to perform non-linear static analyses. Mechanical properties of masonry were defined according to the New Technical Codes for Constructions (NTC18), assuming a limited knowledge level (LC1). Refined mechanical fragility functions have been derived and compared to the empirical ones. Analysis results have shown that the empirical method tends to overestimate by 5% and 10% the expected damage for slight and moderate thresholds. For PGA values greater than 0, 3 g the damage levels decreased by 30% and 20%, with reference to the near collapse and collapse conditions, respectively. Highlights: For the large-scale prediction of the global vulnerability of an urban sector, macroseismic method is a very useful tool; The use of the use of macroseismic method for the estimation of seismic vulnerability for an isolated masonry building provides good correlation with mechanical approach; The use of mechanical method provides very refine results in term of expected damage than empirical ones; Macroelement approach providing a good results in term of fragility curves since the uncertainties related to the calibration of the fragility curves are intrinsically defined; The empirical method tends to overestimate by 5% and 10% the expected damage for slight and moderate thresholds. Contrary, for PGA values greater than 0, 3 g the damage levels decreased by 30% and 20%, with reference to the near collapse and collapse conditions, respectively.